The Mosses of Crocker Range Park, Malaysian Borneo - Monica Suleiman; Dunstan Polus Masundang; Hiroyuki Akiyama (Pensoft Publishers, 2017)
This paper reports the mosses from Crocker Range Park (CRP) in Sabah, Malaysian Borneo. In total, 293 species, three subspecies and eight varieties belonging to 118 genera and 36 families are reported. This represents about 40% and 47% of the species and infra-specific taxa reported from Borneo and Sabah, respectively. Out of these, six species are new records for Borneo, namely Barbella horridula, Chaetomitrium lancifolium, Distichophyllum leiopogon, Rhaphidostichum luzonense, Rosulabryum capillare and Taxiphyllum taxirameum and 12 species and one variety are new to Sabah. With these additions, the current number of mosses in Sabah and Borneo are 651 and 766, respectively. The largest family of mosses is Calymperaceae with 35 species and one subspecies, followed by Sematophyllaceae with 32 species and two varieties and Pylaisiadelphaceae with 21 species and one variety. In conclusion, CRP has a very high species richness of mosses which is the second highest in Borneo, after Mount Kinabalu.